2009
DOI: 10.1007/s11948-009-9120-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Research in Delirium: Arguments for Including Decisionally Incapacitated Subjects

Abstract: Here we describe how more important findings were obtained in a delirium study by using an informal assessment of mental capacity, and, in those who lacked capacity, obtaining consent later when or if capacity returned or a proxy was found. From a total of 233 patients 23 patients lacked capacity as judged by our informal capacity judgment and 210 did not. Of those who lacked capacity, 13 agreed to enter in the study. Six of them regained capacity later. When these 13 participants were excluded from analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 12 publications
3
27
0
17
Order By: Relevance
“…Including only delirious subjects with capacity to consent can lead to selection bias with reduced generalisability of results. Such effects have been demonstrated in the Adamis et al sample, where exclusion from analysis of incapacitated participants showed that the significant association of IGF-I and delirium were no longer evident [125]. Thus, the informed consent process can be an important factor which has been underestimated in delirium studies and is an important source of bias.…”
Section: Methodological Critique Of the Studiesmentioning
confidence: 99%
“…Including only delirious subjects with capacity to consent can lead to selection bias with reduced generalisability of results. Such effects have been demonstrated in the Adamis et al sample, where exclusion from analysis of incapacitated participants showed that the significant association of IGF-I and delirium were no longer evident [125]. Thus, the informed consent process can be an important factor which has been underestimated in delirium studies and is an important source of bias.…”
Section: Methodological Critique Of the Studiesmentioning
confidence: 99%
“…Patients in agreement, but lacking capacity and with no available relatives, were entered in the study until they regained capacity or relatives were contactable. This was in accordance with previous research in delirium and the ethics committee approval …”
Section: Methodsmentioning
confidence: 99%
“…We used an informal capacity assessment to minimize such bias; however, it is possible that such selection or spectrum bias could falsely elevate PrEDICT specificity. 11,40 But other ethical approaches, including timing consent during lucid intervals, using plain language informed consent materials, and using proxies for consent when appropriate, could be considered. 12 Regardless, the PrEDICT application should be validated in a larger patient population prior to clinical use.…”
Section: Limitationsmentioning
confidence: 99%